PENGARUH PROFESIONALISME AUDITOR, INDEPENDENSI AUDITOR, ETIKA PROFESI, BUDAYA ORGANISASI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI BALI - Lukyta Arumsari, Adelia; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
This research aims to test the impact of auditor professionalism, auditor independence, professional ethics, organizational culture and leadership style to the auditor performance at Public Accounting Firms in Bali. Data is collected using survey method with questionnaire technique. The target of respondent in this research is 60 respondents, but respondent’s data that can be processed is only 56 questionnaire answers. The data analysis technique used is multiple linear regression . The result of research shows that auditor professionalism, auditor independence, professional ethics, organizational culture and leadership style provide positive impact to the auditor performance. Key words : auditor professionalism, auditor independence, professional ethics, organizational culture, leadership style and auditor performance.
Keywords: auditor professionalism, auditor independence, professional ethics, organizational culture, leadership style and auditor performance.